Endophytic fungal communities associated with field-grown soybean roots and seeds in the Huang-Huai region of China - Hongjun Yang; Wenwu Ye; Jiaxin Ma; Dandan Zeng; Zhenyang Rong; Miao Xu; Yuanchao Wang; Xiaobo Zheng (PeerJ, 2018)
Plants depend on beneficial interactions between roots and fungal endophytes for growth, disease suppression, and stress tolerance. In this study, we characterized the endophytic fungal communities associated with the roots and corresponding seeds of soybeans grown in the Huang-Huai region of China. For the roots, we identified 105 and 50 genera by culture-independent and culture-dependent (CD) methods, respectively, and isolated 136 fungal strains (20 genera) from the CD samples. Compared with the 52 soybean endophytic fungal genera reported in other countries, 28 of the genera we found were reported, and 90 were newly discovered. Even though Fusarium was the most abundant genus of fungal endophyte in every sample, soybean root samples from three cities exhibited diverse endophytic fungal communities, and the results between samples of roots and seeds were also significantly different. Together, we identified the major endophytic fungal genera in soybean roots and seeds, and revealed that the diversity of soybean endophytic fungal communities was influenced by geographical effects and tissues. The results will facilitate a better understanding of soybean–endophytic fungi interaction systems and will assist in the screening and utilization of beneficial microorganisms to promote healthy of plants such as soybean.